The incessant cases of pedophilia in Nigeria: law to the rescue? (2022)
In the last decade, statistics have shown that sexual offences are on the increase. However, one of such offences generating serious concern in Nigeria and other parts of Africa is the unusual sexual interactions between a male adult and the girl child. Sometimes, this act occurs between biologically related persons, for example, between a father and his girl child. This social behaviour is clearly differentiated from other sexual offenses, such as rape, indecent assault on females, defilement, and other acts classified as unnatural offences which are expressly provided for in both the Criminal Code Act and Penal Code Law. Until the last two decades, adult sexual disorder which consists of adult's desire for sexual gratification through child molestation, particularly among prepubescent children was not prevalent. This paper seeks to examine the factors responsible for the frequency of pedophilia in Nigeria, its effects on society, and the adequacy of law or otherwise to curb the menace. The possibility of using other instruments for the total eradication of the act or such that will deter persons with such traits outside the legal instrument will be considered. This work will make recommendations that seek to either totally eradicate the practice or reduce its incidence.